Synthesis of novel tetrazol-pyridine based cationic Ir(III) complexes with efficient AIE characteristic and significant mechanochromic luminescence behavior. (January 2021) - Zhao, Kai-Yue; Song, Wei-Lin; Yang, Yang; Duan, Ying-Chen; Li, Guang-Fu; Shan, Guo-Gang; Fu, Qiang; Su, Zhong-Min
Abstract: Three new cationic Ir(III) complexes with donor-acceptor (D-A) type ligands, in which a 2-(1 H -tetrazol-5-yl)pyridine unit as an electron acceptor and carbazole-based functional moiety as an electron donor, namely Ir-TA-CzDBr, Ir-TA-CzBr and Ir-TA-Cz, are synthesized and characterized. All complexes exhibit obvious aggregation-induced emission (AIE) activities with weak emission in diluted solution but bright light in the aggregation state. The present AIE mechanism was also elucidated by performing the comprehensive theoretical calculation. Moreover, the Ir(III) complexes show excellent reversible mechanochromic luminescent (MCL) behaviors and the emission colors in powder can be switched by grinding and fuming. The reversible, naked-eye visible and efficient mechanochromism of designed Ir(III) complexes paves the way toward the potential application in the field of reversible writing/erasing paper. Graphical abstract: Novel classes of Ir(III) complexes with functional tetrazol-pyridine units as ligands were designed and synthesized, which exhibit efficient aggregation-induced emission as well as mechanochromic luminescent behaviors. Image 1 Highlights: Novel cationic Ir(III) complexes with tetrazol-pyridine ligands were synthesized. All complexes exhibit obvious aggregation-induced emission (AIE) properties. Possible AIE mechanism were studied by carried out the theoretical calculations. They also show reversible mechanochromic luminescent behaviors in solid-state.